DENTAL SERVICE UNDER THE CONDITIONS OF MANDATORY HEALTH INSURANCE - Елена Александровна Тё; Игорь Анатольевич Тё; Елена Александровна Киселева; Динар Минзагитович Гарафутдинов; Сергей Владимирович Черненко; Вадим Гельевич Мозес; Елена Владимировна Рудаева; Светлана Ивановна Елгина; Кира Борисовна Мозес; Яэль Центер (Медицина в Кузбассе)
In order to obtain complete and objective information about the state of the dental service of the Kemerovo region, in order to find out the causes of existing problems, develop ways and mechanisms to solve them, as well as formulate the main provisions of the mechanism of the system of continuous improvement of the quality of dental care, a comprehensive multi-level sociological study was conducted, including among doctors and patients of dental clinics. 247 dentists and 740 patients of Kuzbass dental clinics selected as pilot facilities were interviewed.